Correction: Engineering spin and antiferromagnetic resonances to realize an efficient direction-multiplexed visible meta-hologram. Issue 2 (15th January 2020) - Ansari, Muhammad Afnan; Kim, Inki; Rukhlenko, Ivan D.; Zubair, Muhammad; Yerci, Selcuk; Tauqeer, Tauseef; Mehmood, Muhammad Qasim; Rho, Junsuk
Abstract : Correction for 'Engineering spin and antiferromagnetic resonances to realize an efficient direction-multiplexed visible meta-hologram' by Muhammad Afnan Ansari et al., Nanoscale Horiz., 2020, 5, 57–64.